Network Formation with Publicly Noxious but Privately Profitable Agents: An Experiment - Antonio Cabrales; Gema Pomares; David Ramos Mu\~noz; Angel Sánchez (CESifo GmbH, 2025)
We study experimentally a new model to study the effect of climate externalities and contractual incompleteness on network formation. We model a network where good/green firms enjoy direct and indirect benefits from linking with one another. Bad/brown firms benefit from having a connection with a good firm, but they are a cost to both direct and indirect connections. In efficient networks the green firms should form large connected components with very few brown firms attached. The equilibrium networks, on the other hand, have many more brown firms attached, and components are also smaller than the efficient ones. Our experiments show that empirical results are broadly in line with the theoretical equilibrium predictions, although the precise quantitative outcomes are different from the theory.
Keywords: C92; D62; D85; Q54; 330; network formation; climate change; contractual externalities; efficiency and equilibrium